IN THE AWAKENING OF INDIA'S 'SELF' LITERATURE OF AKHIL BHARATIYA SAHITYA PARISHAD - Bharat Thakor (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sri Aurobindo had said that the intellectual decline of any great nation always begins with the degradation of three qualities. These three qualities are- the ability to think judiciously, to compare and differentiate and to express. These three qualities are related to the study of philosophy, thinking, literature and history etc. Discussion has been an ancient tradition of India. This tradition has been constantly evolving. As a result of this, some idea has been propounded, yet questions have been raised from time to time regarding its usefulness and uselessness. And an attempt was made to answer it. The external world and the internal world were analyzed. The conclusions that were found were compiled and an attempt was made to give them direction. If any conclusion was useless due to the influence of time. It is the nature of consciousness, it is always changing but when something changes, it does not happen in one direction only. It is universally accepted that literature has evolved, but it is also necessary to see and understand how it has evolved. Our culture, religion, philosophy, devotion, Vedic knowledge, science, rituals, civilization, literature, music, history and our way of life are ancient and ever new. Literature makes this flow continuous and eternal.